Analysis of methods and algorithms for processing unstructured text data based on JSON technology - Kucherenko, Yehor; Kulakovska, Inessa (Technology audit and production reserves (Online), 2024)
The object of research is the process of automating systems for structuring data from several sources. The subject of the research is methods and algorithms for implementing a complete system for automated and parallel processing, validation and structuring of data. One of the most problematic areas is the merging of databases with different structures and several common fields into a generalized structure. The research was aimed at developing a system to increase the efficiency of automation of big data processing. As a result of the work, optimization methods were studied, the influence of their internal parameters on the operation of algorithms was analyzed, their main advantages and disadvantages were determined, and software was developed in which the corresponding methods were implemented. An algorithm for structuring data before processing has been obtained. Data structuring is achieved by performing the «mapping» operation. Mapping can take place by indexes of already cleaned data or using a defined dictionary with a given set of keys, which allows not to care about the sequence of storing values and their possible shift. The practical significance of the developed system lies in the improvement of methods of collecting and processing information for the purpose of its further validation, cleaning and accumulation in the following categories: geographic addresses and geo-coordinates, validation and automated addition of a mobile phone number to the international format, processing of car numbers (in modern and outdated format), VIN code of the engine and car brand, validation of urls of social networks, passport data and processing of personal data. Compared to similar methods for processing large volumes of data, the possibility of splitting the input file or stream into separate parts was used, the cleaned data from which is combined at the end of the system operation. Thanks to this, it is possible to process data whose size exceeds the available volume of the device's RAM, and the method of working with loosely structured text files in CSV format has been improved. Об’єктом дослідження є процес автоматизації систем для структуризації даних з декількох джерел. Предметом дослідження є методи та алгоритми реалізації цілісної системи для виконання автоматизованої та паралельної обробки, валідації та структуризації даних. Одним із найбільш проблемних місць є злиття баз даних із різними структурами та декількох спільними полями в узагальнену структуру. Дослідження було направлено на розробку системи для підвищення ефективності автоматизації обробки великих даних. В результаті виконання роботи було досліджено методи оптимізації, проаналізовано вплив їх внутрішніх параметрів на роботу алгоритмів, визначені основні їх переваги та недоліки, а також розроблено програмне забезпечення, в якому реалізовані відповідні методи. Отримано алгоритм структуризації даних перед їх обробкою. Структуризація даних досягається шляхом виконання операції «маппінгу». Маппінг може відбуватися за індексами вже очищених даних або з використанням визначеного словника з заданим набором ключів, що дозволяє не піклуватися про послідовність зберігання значень та їх можливий зсув. Практична значимість розробленої системи полягає у вдосконаленні методів збору та обробки інформації з метою її подальшої валідації, очистки та накопичення за наступними категоріями: географічні адреси та гео-координати, валідація та автоматизоване доповнення номеру мобільного телефону до міжнародного формату, обробка автомобільних номерів (у сучасному та застарілому форматі), VIN-коду двигуна та марки автомобіля, валідація url-адрес соціальних мереж, паспортні дані та обробка персональних даних. У порівнянні з аналогічними методами для обробки даних великого об’єму була використана можливість розбиття вхідного файлу або потоку на окремі частини, очищенні дані з яких – об’єднуються наприкінці процесу роботи системи. Завдяки цьому забезпечується можливість обробки даних, розмір яких перевищує доступний об’єм оперативної пам’яті пристрою, покращено методику роботи з слабоструктурованими текстовими файлами у форматі CSV.